1999
DOI: 10.1136/jcp.52.5.376
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole versus itraconazole for the prevention of fungal infections in haemato-oncology.

Abstract: Conclusions-In neutropenic patients treated for haematological malignancies with or without autologous stem cell transplantation, fluconazole and itraconazole in low doses result in a similar low frequency of fungal disease. Fluconazole may be the preferable drug because of the smaller number of capsules and lack of need for timing relative to meals. (J Clin Pathol 1999;52:376-380)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 26 publications
1
45
0
1
Order By: Relevance
“…22,23 Doses lower than 400 mg/d failed to show a marked benefit and have not been carried out in a placebo controlled fashion. 17,[24][25][26][27] Since moulds and Candida krusei, harbor intrinsic resistance to fluconazole and only dose dependent activity against Candida glabrata, breakthrough infections with these fungi have occurred. 16,21,23,28,29 The clinical relevance of the development of resistance during fluconazole prophylaxis is still a matter of debate, 30,31 while a general shift towards higher rates of strains exhibiting primary resistance have been clearly shown in the intensive care setting.…”
Section: Azolesmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Doses lower than 400 mg/d failed to show a marked benefit and have not been carried out in a placebo controlled fashion. 17,[24][25][26][27] Since moulds and Candida krusei, harbor intrinsic resistance to fluconazole and only dose dependent activity against Candida glabrata, breakthrough infections with these fungi have occurred. 16,21,23,28,29 The clinical relevance of the development of resistance during fluconazole prophylaxis is still a matter of debate, 30,31 while a general shift towards higher rates of strains exhibiting primary resistance have been clearly shown in the intensive care setting.…”
Section: Azolesmentioning
confidence: 99%
“…Itraconazole capsules lead to adequate plasma levels with delay, if at all, and thus are not recommended as a start-up for prophylaxis of invasive fungal infection. 27,33,34 A superior bioavailability is achieved with itraconazole oral suspension. A double-blind, double dummy, placebo controlled trial comparing the suspension at a dose of 2.5 mg/kg bid plus nystatin 500.000 IU qid to nystatin alone found a more effective reduction in the rate of fatal candidemia from 2% to zero.…”
mentioning
confidence: 99%
“…Nonetheless, these fungal infection-related mortality rates are comparable to those reported from other clinical studies evaluating fluconazole and itraconazole (fluconazole, 1.2-3.0%; itraconazole, Ͻ 1.0 -15.2%). 8,9,12,[15][16][17] In addition, no prophylaxis-related deaths occurred with either lipid-based amphotericin B product.…”
mentioning
confidence: 96%
“…[1][2][3] In view of the poor prognosis of disseminated fungal disease, many centres administer antimycotic agents prophylactically. Fluconazole has emerged as the most widely used prophylactic agent in neutropenic patients and has been used in doses varying from 50 to 400 mg. [4][5][6][7][8][9][10] Its optimal dose in antifungal prophylaxis remains to be determined. 5,6 Not only has fluconazole been found to be highly effective in eliminating colonisation and infection by Candida spp.…”
mentioning
confidence: 99%
“…In a recent randomised trial we reported a 100% mortality in patients with proven fungal infections due to Aspergillus or Mucor spp., the overall incidence of such infections in our population being 5%. 10 In an attempt to reduce both incidence of, and mortality from these infections, an open-label, randomised clinical trial was initiated, to compare the safety and efficacy of intravenous ABCD with oral fluconazole in the prevention of fungal disease in neutropenic patients with haematological malignancies. For the prophylactic use of ABCD we decided to administer half of the daily dose that is generally recommended for antifungal therapy.…”
mentioning
confidence: 99%